2016
DOI: 10.1002/cncr.30073
|View full text |Cite
|
Sign up to set email alerts
|

Open‐label, multicenter, phase 1 study of alisertib (MLN8237), an aurora A kinase inhibitor, with docetaxel in patients with solid tumors

Abstract: Alisertib at 20 mg twice daily on days 1 to 7 with intravenous docetaxel at 75 mg/m(2) on day 1 in a 21-day cycle was well tolerated, and the combination demonstrated antitumor activity. Cancer 2016;122:2524-33. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…49 In our study, this was exemplified by patient #35153 where some of the emerging somatic alterations, such as loss of PTEN or RB1 and the novel gain of 20q13, which harbors the AURKA gene, have been reported as frequent changes in t-NEPC [50][51][52][53][54] and represent a potential therapeutic target. 55 AR antagonism may induce lineage alterations and thus promote enhanced lineage plasticity, 19,[52][53][54]56 as previously reported by us and others. 11,19 Furthermore, we describe several cases in which genomic alterations evolve with disease progression, but at present it is unclear whether these are associated with response/resistance to abiraterone/ enzalutamide.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…49 In our study, this was exemplified by patient #35153 where some of the emerging somatic alterations, such as loss of PTEN or RB1 and the novel gain of 20q13, which harbors the AURKA gene, have been reported as frequent changes in t-NEPC [50][51][52][53][54] and represent a potential therapeutic target. 55 AR antagonism may induce lineage alterations and thus promote enhanced lineage plasticity, 19,[52][53][54]56 as previously reported by us and others. 11,19 Furthermore, we describe several cases in which genomic alterations evolve with disease progression, but at present it is unclear whether these are associated with response/resistance to abiraterone/ enzalutamide.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, this was exemplified by patient #35153 where some of the emerging somatic alterations, such as loss of PTEN or RB1 and the novel gain of 20q13, which harbors the AURKA gene, have been reported as frequent changes in t-NEPC 5054 and represent a potential therapeutic target 55 . AR antagonism may induce lineage alterations and thus promote enhanced lineage plasticity 19, 5254, 56 , as previously reported by us and others 11, 19 .…”
Section: Discussionmentioning
confidence: 82%
“…Our analysis of MCF10A cells showed that non-transformed cells do display nuclear abnormalities and arrested proliferation in response to alisertib treatment, which warrants an assessment of long-term effects on normal tissues. Clinically, antitumor effects of alisertib were reported in solid and hematological cancers [4345], and long-term progression-free survival or complete response was observed in some cases in patients with solid cancers or in patients with recurrent ovarian cancer [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Alisertib (MLN8237) is an orally available ATP-competitive, highly selective inhibitor of AURKA (40-fold selective for AURKA compared with AURKB) [24]. Clinical trials testing Alisertib as a single agent or in combination with conventional chemotherapies are ongoing for the treatment of various malignancies [14,[25][26][27][28][29][30][31][32][33]. Of the entire AURKA inhibitors, only Alisertib has proceeded to phase III evaluation [34].…”
Section: Discussionmentioning
confidence: 99%